2007
DOI: 10.1007/s00436-007-0548-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of IgG antibodies to recombinant Plasmodium falciparum 732var CIDR-1α domain in mothers and their newborn babies

Abstract: Different domains of a novel full-length var gene (termed 732var) isolated from a placenta of a malaria-infected woman were expressed in Escherichia coli as recombinant proteins and analysed biochemically and immunologically. Two of these, the Duffy binding-like (DBL)-3gamma domain and the cysteine-rich interdomain region (CIDR)-1alpha were able to bind chondroitin sulfate A and CD36, respectively. The DBL-3gamma domain was investigated in a previous study and confirmed here to exhibit anti-disease characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The low incidence of symptomatic malaria below the age of six months has been attributed to the presence of fetal hemoglobin [14,15] and passively acquired maternal IgG [5]. Malaria-specific antibodies at birth (in maternal and/or cord blood) have also been associated with protection against some malaria parasite antigens [5,[16][17][18][19][20]. Nevertheless, detailed descriptions of the longitudinal patterns of symptomatic malaria and asymptomatic infections within the first year of life are not available, as most research focuses primarily on the direct effects of clinical symptoms [10,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The low incidence of symptomatic malaria below the age of six months has been attributed to the presence of fetal hemoglobin [14,15] and passively acquired maternal IgG [5]. Malaria-specific antibodies at birth (in maternal and/or cord blood) have also been associated with protection against some malaria parasite antigens [5,[16][17][18][19][20]. Nevertheless, detailed descriptions of the longitudinal patterns of symptomatic malaria and asymptomatic infections within the first year of life are not available, as most research focuses primarily on the direct effects of clinical symptoms [10,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is further strengthened by reports of non-immune HbS children with high parasitemias and severe malaria [36], and could be more rigorously tested by studying non-immune hemoglobinopathic individuals who acquire malaria. Our findings indicate that measurements of PfEMP-1-specific antibody levels are likely to be particularly relevant and informative in studies of infant immunity to malaria [37], [38], [39].…”
Section: Discussionmentioning
confidence: 86%
“…Longitudinal studies designed to answer this question vary in regards to antigens studied, reported outcomes (infection vs clinical disease), method for detecting parasitaemia, location and transmission intensity. A few of these studies have demonstrated an association between maternal antimalarial antibodies and protection from infection (Deloron et al 1997 ; Khattab et al 2007 ), clinical disease (Hogh et al 1995 ) or both (Branch et al 1998 ) in infants. However, several others have found an association between maternal antibodies and an increased risk for infection in infants (Riley et al 2000 ; Cot et al 2003 ; Kangoye et al 2014 ), or no association at all (Mutabingwa et al 1993 ; Achidi et al 1996 ; Deloron et al 1997 ; Riley et al 2000 ; Zhou et al 2002 ; Kangoye et al 2014 ; Apinjoh et al 2015 ).…”
Section: Maternal Antimalarial Antibodies In the Young Infant: Role Omentioning
confidence: 99%
“…It is important to consider that different antigens have been used as markers of Pf infection so there is very little consistency between studies. In a study of malaria-exposed pregnant women in Senegal, Khattab et al showed that maternal antibodies against the 732var Pf erythrocyte membrane protein 1 (PfEMP1) domain cysteine-rich interdomain region 1 α (CIDR1 α ) conferred protection against malaria in infants during the first 6 months of life (Khattab et al 2007 ). In another study of anti-VSA antibodies, Cot et al showed that the presence of maternal antibodies against CSA–VSA was associated with a decreased time to first parasitaemia (Cot et al 2003 ).…”
Section: Maternal Antimalarial Antibodies In the Young Infant: Role Omentioning
confidence: 99%